Pengembangan Media Pembelajaran (Modul) berbantuan Geogebra Pokok Bahasan Turunan - Sari, Fiska Komala; Farida, Farida; Syazali, M. (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
This research is motivated by the lack of learning media used by educators in the teaching and learning process, and the low interest and motivation of students. The purpose of this research is to find out how the feasibility of developing Geogebra-assisted learning media (modules) is a subject matter. The research method used is research and development (R n D) with the steps used based on Sugiyono. The steps taken are limited to seven stages: 1) Potential and problems, 2) Data collection, 3) Product Design, 4) Design validation, 5) Design improvements, 6) Product trials, 7) Product revision, due to time constraints - the research steps according to Sugiyono were not carried out by all. The results of the study were based on the results of the test of material experts, media experts and linguists, scores obtained in succession (4.08), (4.53), and (4.27), the Geogebra-assisted learning module was assessed for interesting and feasible categories to be used as learning media for high school class XI on the topic of derivatives.